# |
ODE |
Mathematica |
Maple |
\[
{}y-x y^{2}+\left (x +x^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2} y^{4} \left (x y^{\prime }+y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y+x^{2} y^{5} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{2}-y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x}+\frac {x^{3}}{y}+x \tan \left (\frac {y}{x^{2}}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-3 y = x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{2 x}}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}+x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = 2 x \csc \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 y-x^{3} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y-x +x y \cot \left (x \right )+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 6 x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x \ln \left (x \right ) y^{\prime }+y = 3 x^{3}
\] |
✓ |
✓ |
|
\[
{}y-2 x y-x^{2}+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{3} x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime } x +y^{3} = x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x y^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{y}-2 x y\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = y^{\prime } y^{2} {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 = x^{3} \left (y-1\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x^{2} y+y \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sin \left (2 x \right ) = 2 y+2 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1-x y\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+1+\left (2 y-3 x +5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{2} = \left (x^{3}-x y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{3}+y = \left (y^{2} x^{3}-x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2}+x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y^{2}+x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{x}-3 x^{2} y^{2}\right ) y^{\prime }+y \,{\mathrm e}^{x} = 2 x y^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2}+y = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}6 x +4 y+3+\left (3 x +2 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x +y\right ) = x \sin \left (x +y\right )+x \sin \left (x +y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2} {\mathrm e}^{x y}+\cos \left (x \right )+\left ({\mathrm e}^{x y}+y \,{\mathrm e}^{x y} x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \ln \left (x -y\right ) = 1+\ln \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = {\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{2}-3 x y-2 x^{2} = \left (x^{2}-x y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = 4 x^{3}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )+{\mathrm e}^{x} \cos \left (y\right ) y^{\prime } = y \sin \left (x y\right )+x \sin \left (x y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \left (1+x \right ) = \left (x \,{\mathrm e}^{x}-y \,{\mathrm e}^{y}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{4}+x^{6}-x^{3} y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+3 y \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\frac {y}{x}-\frac {y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y \,{\mathrm e}^{\frac {x^{2}}{y^{2}}}}{y^{2}+y^{2} {\mathrm e}^{\frac {x^{2}}{y^{2}}}+2 x^{2} {\mathrm e}^{\frac {x^{2}}{y^{2}}}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +2 y+2}{y-2 x}
\] |
✓ |
✓ |
|
\[
{}3 x^{2} \ln \left (y\right )+\frac {x^{3} y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {3 y^{2}}{x^{2}+3 x}+\left (2 y \ln \left (\frac {5 x}{x +3}\right )+3 \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y-x}{\left (x +y\right )^{3}}-\frac {2 x y^{\prime }}{\left (x +y\right )^{3}} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y-y^{3}-\left (3 x y^{2}-x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x^{2}+1\right ) y^{\prime }+2 y = \left (x^{2}+1\right )^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-3 x -2 y-1}{2 x +3 y-1}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x^{2} y} \left (1+2 x^{2} y\right )+x^{3} {\mathrm e}^{x^{2} y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} {\mathrm e}^{y}-2 x +\left (x^{3} {\mathrm e}^{y}-\sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x y+y^{2}+\left (3 x y+x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}+x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2} \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\frac {\cos \left (y\right )}{x +3}-\left (\sin \left (y\right ) \ln \left (5 x +15\right )-\frac {1}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+y-1+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-y^{2} = 2 x y
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x \cot \left (y \right ) = \sec \left (y \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 3 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 3 t^{2}+4 t
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = b \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {1}{\sqrt {t^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {\cos \left (t \right )}{\sin \left (t \right )}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x^{2}-3 x+2
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = b \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \left (x-1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \sqrt {x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 2 \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \tan \left (x\right )
\] |
✓ |
✓ |
|
\[
{}3 t^{2} x-t x+\left (3 t^{3} x^{2}+t^{3} x^{4}\right ) x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+2 x+\left (-t^{2}+4\right ) x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \cos \left (\frac {x}{t}\right )
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}-x^{2}\right ) x^{\prime } = t x
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{3 t} x^{\prime }+3 x \,{\mathrm e}^{3 t} = 2 t
\] |
✓ |
✓ |
|
\[
{}2 t +3 x+\left (3 t -x\right ) x^{\prime } = t^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+2 x = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x \tan \left (t \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime }-x \tan \left (t \right ) = 4 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}t^{3} x^{\prime }+\left (-3 t^{2}+2\right ) x = t^{3}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+2 t x+t x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime }+x \ln \left (t \right ) = t^{2}
\] |
✓ |
✓ |
|
\[
{}t x^{\prime }+x g \left (t \right ) = h \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -\lambda x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+c y = a
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {1-y^{2}}\, \arcsin \left (y\right )}{x}
\] |
✓ |
✓ |
|
\[
{}v^{\prime }+u^{2} v = \sin \left (u \right )
\] |
✓ |
✓ |
|
\[
{}v^{\prime }+\frac {2 v}{u} = 3
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\sqrt {\frac {1-y^{2}}{-x^{2}+1}} = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = b \left (1+x^{2} y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = k \left (A -n x\right ) \left (M -m x\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\frac {1}{x}-\frac {1}{y^{2}+2}-\frac {1}{x \left (y^{2}+2\right )}
\] |
✓ |
✓ |
|